Outcomes and factors associated with early mortality in pediatric postcardiotomy veno‐arterial extracorporeal membrane oxygenation. Issue 1 (4th August 2020) - Jin, Yu; Feng, Zhengyi; Zhao, Ju; Hu, Jinxiao; Tong, Yuanyuan; Guo, Shengwen; Zhang, Peiyao; Bai, Liting; Li, Yixuan; Liu, Jinping
Abstract: Mortality and morbidity of children received veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) support after cardiac surgery remain high despite remarkable advances in medical management and devices. The purpose of this study was to describe outcomes and risk factors of applying VA‐ECMO in the surgical pediatric population. We retrospectively analyzed 85 consecutive pediatric patients (aged <18 years) who received postcardiotomy VA‐ECMO from January 2010 to December 2018. Median (IQR) age at ECMO implantation in this cohort was 12.7 (6.4, 43.2) months, median weight was 8.5 (6.0, 12.8) kg, mean ECMO duration was 143.2 ± 81.6 hours and mean hospital length of stay was 48.4 ± 32.4 days. Seventy‐five patients (88.2%) were indicated for postcardiotomy cardiogenic shock. The successful ECMO weaning rate was 70.6% and in‐hospital mortality was 52.9%. The most common diagnosis was transposition of great arteries (n = 18, 21.2%), while acute kidney injury occurred most often (n = 64, 75.3%). Multivariate logistic regression analysis showed that thrombocytopenia, hemolysis, and nosocomial infection were positively correlated with in‐hospital mortality. Multivariate Cox proportional hazard regression analysis presented that thrombocytopenia significantly increased the 180‐day mortality in patients with successful weaning. Therefore, multiple factors had adverse effects on prognosis. Patient selection and procedures from ECMO implantation to weaning need to be closely monitored and performed in a timely manner to improve outcome.